Analisis dan Desain Sistem Informasi Akademik Pada SMP Al-Falah Assalam Tropodo 2 Sidoarjo - Puspitarini, Meidiana; Sunarto, Dewiyani; Wulandari, Sri Hariyani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Junior high school Al-Falah Assalam Tropodo 2 has a number of students ranging from grade 7 to grade 9 as many as 630 students, at any level of the hierarchy there are 7 classes and each class has 30 students. With the current number of students, the school experienced a problem with timeliness and accuracy of the content. Timelinessand accuracy of the content in question is the number of data that must be processed at the time when the school administration management processes such as data processing value data of students, students ' attendance data, data ontuition and student report cards processing is done manually. This resulted in a report on the administration of the school could not be completed on time and the result ofthe process of charging data become less accurate. Based on the above issues, the school wanted to devise a system of academic information wake. Analysis and designof academic information systems on SMP Al-Falah Assalam Tropodo 2 it generatesdocuments in the form of specification of the needs oftheDeviceSoftware (SKPL)Designand software architecture (DAPL). The document can be used as the basis for software development. The hope, after the designwas developed to overcome existing problems on SMP Al-Falah Assalam Tropodo 2 Sidoarjo.